2005
DOI: 10.1073/pnas.0501440102
|View full text |Cite
|
Sign up to set email alerts
|

Visual working memory in decision making by honey bees

Abstract: The robustness and plasticity of working memory were investigated in honey bees by using a delayed matching-to-sample (DMTS) paradigm. The findings are summarized as follows: first, performance in the DMTS task decreases as the duration between the presentation of the sample stimulus and the presentation of the comparison stimuli is increased. This decrease is well approximated by an exponential decay function. Performance is significantly better than random-choice level even at delays as long as 5 sec and is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(86 citation statements)
references
References 34 publications
(30 reference statements)
2
83
0
Order By: Relevance
“…In this paradigm, a bee has to keep a transient nonassociative memory of the sample stimulus and then apply a learned rule to choose the right stimulus. The largest effective time interval between the sample was ϳ5 s (Zhang et al, 2005), a value close to the 6 s odor trace found here (Fig. 2 B).…”
Section: Neural Substrate Of the Odor Trace: A Place For Kenyon Cells?mentioning
confidence: 49%
“…In this paradigm, a bee has to keep a transient nonassociative memory of the sample stimulus and then apply a learned rule to choose the right stimulus. The largest effective time interval between the sample was ϳ5 s (Zhang et al, 2005), a value close to the 6 s odor trace found here (Fig. 2 B).…”
Section: Neural Substrate Of the Odor Trace: A Place For Kenyon Cells?mentioning
confidence: 49%
“…These results document that bees learn rules relating stimuli in their environment. The capacity of honeybees to solve DMTS tasks has recently been verified (Zhang et al, , 2005. It was found that the working memory for the sample underlying the solving of DMTS is ,5 s (Zhang et al, 2005) and thus coincides with the duration of other visual and olfactory short-term memories characterized in simpler forms of associative learning in honeybees (see Section 1.26.6).…”
Section: Rule Learningmentioning
confidence: 99%
“…It was found that the working memory for the sample underlying the solving of DMTS is ,5 s (Zhang et al, 2005) and thus coincides with the duration of other visual and olfactory short-term memories characterized in simpler forms of associative learning in honeybees (see Section 1.26.6). Moreover, bees trained in a DMTS task can learn to pay attention to one of two different samples presented successively in a flight tunnel (either to the first or to the second) and can transfer the learning of this sequence weight to novel samples (Zhang et al, 2005).…”
Section: Rule Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…In this experimental framework, bees can learn, through experience, to navigate in complex mazes (12), to categorize objects based on coincident visual features (11,(13)(14)(15), and to master discriminations based on identity (16,17) and numerosity (18)(19)(20). Bees can also learn the concept of above/ below with respect to a constant reference (e.g., a horizontal line) (21), but whether bees can reach a level of abstraction allowing them to master multiple concepts simultaneously is an intriguing question that currently remains unknown and that goes beyond all previous attempts to characterize cognitive power of insect brains (22).…”
mentioning
confidence: 99%